Efficacy and Safety of Electroacupuncture for Insomnia Disorder: A Multicenter, Randomized, Assessor-Blinded, Controlled Trial - Lee B (Dove Medical Press, 2020)
Boram Lee,1 Bo-Kyung Kim,2 Hyeong-Jun Kim,3 In Chul Jung,4 Ae-Ran Kim,1 Hyo-Ju Park,1 O-Jin Kwon,1 Jun-Hwan Lee,1,5 Joo-Hee Kim6,7 1Clinical Medicine Division, Korea Institute of Oriental Medicine, Daejeon, Republic of Korea; 2Department of Neuropsychiatry, School of Korean Medicine, Pusan National University, Yangsan-si, Gyeongsangnam-do, Republic of Korea; 3Department of Oriental Gynecology, Jecheon Oriental Hospital of Semyung University, Jecheon, Republic of Korea; 4Department of Neuropsychiatry, College of Korean Medicine, Daejeon University, Daejeon, Republic of Korea; 5Korean Medicine Life Science, University of Science & Technology (UST), Campus of Korea Institute of Oriental Medicine, Daejeon, Republic of Korea; 6Department of Acupuncture and Moxibustion Medicine, College of Korean Medicine, Sangji University, Wonju-si, Gangwon-do, Republic of Korea; 7Research Institute of Korean Medicine, Sangji University, Wonju-si, Gangwon-do 26339, Republic of KoreaCorrespondence: Joo-Hee KimDepartment of Acupuncture and Moxibustion Medicine, College of Korean Medicine, Sangji University, 83, Sangjidae-gil, Wonju-si, Gangwon-do, Republic of KoreaTel +82 33 741 9268Fax +82 33 741 9141Email jhkim714v@gmail.comPurpose: To evaluate the efficacy and safety of electroacupuncture in treating insomnia.Patients and Methods: In a multicenter, randomized, assessor-blinded, controlled trial, 150 patients with DSM-5-diagnosed insomnia with Insomnia Severity Index (ISI) scores ≥ 15 were randomly assigned to three different groups that underwent 10 sessions of electroacupuncture, sham-electroacupuncture, or usual care for 4 weeks from October 2015 to June 2016 at four Korean medicine hospitals, Republic of Korea. The primary outcome included the ISI score at Week 4; the secondary outcomes included evaluations of Pittsburgh Sleep Quality Index (PSQI), sleep diary, Hospital Anxiety and Depression Scale (HADS), EuroQoL five dimension (EQ-5D), Patient Global Impression of Change (PGIC), and salivary melatonin and cortisol levels. Assessments were performed at baseline (Week 0) and at Weeks 2, 4, 8, and 12.Results: Compared with the usual care group, electroacupuncture group showed a greater improvement in ISI, PSQI, sleep diary-derived variables and HADS and EQ-5D scores at Week 4. The effects mostly persisted until Week 12. There were no significant differences between electroacupuncture and sham-electroacupuncture groups at Week 4 in all outcome measures, except sleep diary-derived sleep efficiency. However, the ISI score showed a significant difference between these groups at Weeks 8 and 12. Treatment success as per PGIC was significantly and borderline higher for electroacupuncture compared with usual care and sham-electroacupuncture, respectively. No significant changes in salivary melatonin and cortisol levels before and after treatment were observed in all groups. No serious adverse events were reported. Blinding was maintained in the sham-electroacupuncture group.Conclusion: Ten sessions of electroacupuncture can improve the sleep quality of patients with insomnia without serious adverse effects. Thus, it can be recommended as an effective, safe, and well-tolerated intervention.Keywords: electroacupuncture, insomnia, sleep initiation and maintenance disorders, randomized controlled trial